Peptide-conjugated PEGylated PAMAM as a highly affinitive nanocarrier towards HER2-overexpressing cancer cells. Issue 109 (10th November 2016) - Rostami, Iman; Zhao, ZiJian; Wang, ZiHua; Zhang, WeiKai; Zhong, Yeteng; Zeng, Qiang; Jia, XinRu; Hu, ZhiYuan
Abstract : Efficient drug delivery to the tumor cells was carried out with HER2 targeting peptide-conjugated PEGlyted PAMAM. Abstract : Numerous effective polymers have been designed for drug and gene delivery; of these, dendrimers have been a superior nanoplatform for targeted delivery to cancerous tumor cells. Doxorubicin (DOX) is an effective first-line antineoplastic drug encapsulated by dendrimers, which may improve its biological half-life and nonspecific distribution for different cancer treatments. In this investigation, an efficient HER2-targeting nanocarrier was developed with peptide YLFFVFER (H6) functionalized PAMAM dendrimers, which could specifically transport DOX to breast cancer cells. The peptide H6 was proportionally conjugated on the peripheral side of G4 PAMAM dendrimers using bifunctional polyethylene glycol (PEG). Toxicity testing showed that the nanocarriers were nearly non-toxic, whereas the DOX-loaded nanocarriers retained high cytotoxicity for the target cells. Detection of the nanocarriers' affinity towards the HER2 protein was performed by surface plasmon resonance imaging (SPRi), and the resulting equilibrium dissociation constant ( K D value) was 7.4810 × 10 −10 M.